English Vocabulary Acquisition of Grade VII Students of SMPN 6 Satap Kupang - Imelda Hongu; Elvis Albertus Bin Toni; Antonius Padu Dagang (Journal of English Language and Education, 2026)
Vocabulary is a key component of language proficiency, supporting comprehension and communication. This study examined the level of English vocabulary mastery among students in class VII-C at SMPN 6 Satap Kupang Tengah. Using a descriptive quantitative design, all 21 students completed a vocabulary test consisting of written and visual-supported sections to measure receptive vocabulary—the ability to recognize and understand grade-appropriate words. Scores were converted to percentages and classified as Very Low (0–40%), Low (41–60%), Moderate (61–80%), or High (81–100%). Results showed a mean score of 41.0% for the written section (Low) and 36.9% for the visual section (Very Low). Overall, students’ vocabulary mastery was categorized as Low, with most scoring between 25% and 50%. These findings reflect limited exposure to English outside the classroom and highlight the need for targeted vocabulary instruction to enhance students’ English proficiency.